2018
DOI: 10.3390/w10050606
|View full text |Cite
|
Sign up to set email alerts
|

Risk Analysis for Reservoir Real-Time Optimal Operation Using the Scenario Tree-Based Stochastic Optimization Method

Abstract: The inherent uncertainty of inflow forecasts hinders the reservoir real-time optimal operation. This paper proposes a risk analysis model for reservoir real-time optimal operation using the scenario tree-based stochastic optimization method. We quantify the probability distribution of inflow forecast uncertainty by developing the relationship between two forecast accuracy metrics and the standard deviation of relative forecast error. An inflow scenario tree is generated via Monte Carlo simulation to represent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The Dadu River basin [21] is the fifth largest hydropower base in China. It is the main peak shaving and frequency regulation power source for the Sichuan power grid and a key barrier for flood control in the Yangtze River Basin and surrounding area.…”
Section: Overview Of the Study Areamentioning
confidence: 99%
“…The Dadu River basin [21] is the fifth largest hydropower base in China. It is the main peak shaving and frequency regulation power source for the Sichuan power grid and a key barrier for flood control in the Yangtze River Basin and surrounding area.…”
Section: Overview Of the Study Areamentioning
confidence: 99%
“…Seguin et al [16] built a short-term operation ST model for hydropower stations and proved the stability of the model can be maintained with a small amount of calculation. Sun et al [18] established a risk analysis model for real-time optimal discharge of reservoirs based on the ST stochastic optimization method, as well as a risk assessment model based on the principle of maximum entropy.…”
Section: Introductionmentioning
confidence: 99%
“…A study has also shown the utility of forecasting in developing risk analysis models for the optimal operations of a reservoir to reduce flood incidents [6]. According to the International Committee for Weights and Measures, flows in wastewater pipes remain a significant challenge [7], and increased sediment deposition with limited self-cleansing has often led to the reduction of the capacity of wastewater pipes [8,9].…”
Section: Introductionmentioning
confidence: 99%